Product nordhaus-gaddum-type results for the induced path number involving complements with respect to Kn or Kn,n
The induced path number p(G) of a graph G is defined as the minimum number of subsets into which the vertex set of G can be partitioned so that each subset induces a path. A Nordhaus-Gaddum-type result is a (tight) lower or upper bound on the sum (or product) of a parameter of a graph and its complement. If G is a subgraph of H